Biological therapy in the treatment of moderate-to-severe ulcerative colitis patients: Can colectomy be prevented? - Teixeira, Fábio Vieira [UNESP]; Hossne, Rogério Saad [UNESP]; Kotze, Paulo Gustavo; Denadai, Rafael; Miszputen, Sender Jankiel (FapUNIFESP (SciELO), 2011)
Ulcerative colitis treatment intends to induce remission, and its maintenance. Biological drugs, such as infliximab, have been indicated in moderate and severe cases of the disease, which are unresponsive to conventional medication. Randomized controlled trials proved the efficacy of biological treatment with high rates of sustained disease remission and mucosal healing. Recently, the concept of mucosal healing has been inversely associated with surgical treatment. Patients treated with infliximab have lower colectomy rates than those receiving conventional therapies. We suppose that earlier use of biological drugs in disease's course would lead to better clinical control and mucosal healing, with a consequent reduction in colectomy rates. To support this hypothesis, a literature review from January, 1996 to April, 2011 was performed.
Keywords: Biological therapy; Colectomy; Colitis; Treatment outcome; Ulcerative